Characteristics of the match performance of tennis players under 14 years old - Šanjug, S.; Barbaros, P.; Bilic, Z. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
With the advancement of technology increasingly used on tennis courts, it has become possible to track various parameters of sports performance. The aim of this study is to explore the characteristics of male and female tennis players at the Tennis Europe super category tournament for under 14s - Les Petit As, and to determine if there are differences in the characteristics of technical-tactical performance between male and female players using the SwingVision mobile application. A total of 27 parameters were analyzed, which, depending on the aspect of the game they refer to, can be divided into 6 groups: time characteristics of the game, duration of points, success rate of specific shots, shot placement execution, player position on the court during shots and prevalence of specific shots. The results show a high percentage of shots played in the central part of the court and behind the service line. Additionally, male players play more aggressively than female players with a higher percentage of points won in rallies of up to 5 exchanges, also they play more forehand shots to the opponent's backhand and have a higher percentage of successful serves. The results of the study should be taken into account when planning and programming training processes specific to the observed age group and gender of the players.